MANAGEMENT OF GINGIVAL ENLARGEMENT IN PATIENT WITH NON SURGICAL TREATMENT: A CASE REPORT - Watri, Desi; Chuan, How Kim; Halim, Susanna (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
Penyakit gingiva merupakan peradangan pada rongga mulut dan pembengkakan gingiva merupakan salah satu hal yang paling sering ditemukan. Pembesaran gingiva merupakan lesi inflamasi kronis yang disebabkan oleh plak bakteri dan kalkulus. Pembesaran gingiva muncul pada tingkat papila interdental dan/atau jaringan marginal gingiva, dapat terlokalisasi atau menyeluruh. Artikel ini mengkaji kasus pasien yang menderita pembesaran gingiva dan lesi gingiva yang disebabkan oleh plak bakteri. Kasus ini ditangani dengan perawatan periodontal nonsurgical. Selama lima hari, dilakukan terapi antibiotik dan terapi manual. Evaluasi ulang satu bulan kemudian menunjukkan resolusi pembesaran, penurunan peradangan, supurasi, persentase poket periodontal dan penurunan pembengkakan gingiva; perawatan periodontal dilakukan pada saat itu. Setelah tiga bulan, terjadi penurunan persentase poket periodontal dan pembengkakan gingiva; pada saat itu dilakukan terapi periodontal pemeliharaan. ABSTRACTGingiva diseases is an inflammation in oral cavity and gingiva enlargement is one of the most common things found. Gingival enlargement is a chronic inflammatory lesion caused by bacterial plaque and calculus. It appears at the level of interdental papilla and/or marginal gingival tissue, it can be localized or generalized. This article studies a case of a patient who suffered from gingival enlargement and gingival lesions caused by bacterial plaque. This case was managed with the use of nonsurgical periodontal treatment. For five days, antibiotic therapy and manual therapy were performed. Re-evaluation one month later showed resolution of the enlargement, decrease in inflammation, suppuration, percentage of periodontal pockets and decrease gingival swelling; periodontal treatment was performed at that time. After three months, a decrease in the percentage of periodontal pockets and gingival swelling was observed; at that time maintenance periodontal therapy was performed.